2014
DOI: 10.1111/jog.12299
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐Meigs' syndrome associated with hydropic degenerating uterine leiomyoma: A case report

Abstract: Pseudo-Meigs' syndrome secondary to uterine leiomyoma is a rare entity. A 50-year-old Japanese woman presented with a 3-month history of shortness of breath. Chest X-ray and magnetic resonance imaging revealed massive right pleural effusion, ascites and a large subserosal uterine myoma. She underwent a total abdominal hysterectomy with bilateral salpingo-oophorectomy. The pathology was consistent with a benign leiomyoma. The ascites and pleural effusion rapidly disappeared postoperatively. The serum interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Our patient population overall was found to be similar to the patients seen in reported HLM cases from the literature. The patients in our series clinically presented as women of reproductive age (average age 43.79⨦12.7 years), similar to the reported cases from the literature with a median age 42 years (range 26-50) [4,[9][10][11][12][13][14][15][16][17][18][19]. Presenting symptoms of our patients and reported cases resembled those of other female reproductive organ masses [9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our patient population overall was found to be similar to the patients seen in reported HLM cases from the literature. The patients in our series clinically presented as women of reproductive age (average age 43.79⨦12.7 years), similar to the reported cases from the literature with a median age 42 years (range 26-50) [4,[9][10][11][12][13][14][15][16][17][18][19]. Presenting symptoms of our patients and reported cases resembled those of other female reproductive organ masses [9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, one patient's HLM from this study and three reported cases manifested during pregnancy either as acute or chronic complications [10][11][12]. Another unexpected presentation observed in reported cases (seven in total) was pseudo-Meigs syndrome: shortness of breath and pleural effusion with a concurrent pelvic or abdominal mass, elevated serum CA-125, and, in some patients, ascites [13][14][15].…”
Section: Discussionmentioning
confidence: 47%
“…Uterine leiomyomas that present as pseudo-Meigs syndrome have already been described in the literature [11][12][13][14]. However, few cases of pseudo-Meigs syndrome in which a leiomyoma is implanted on the omentum have been reported [15]. In this study, we report a massive abdominopelvic leiomyoma with large ascites in a 22year-old woman.…”
Section: Introductionmentioning
confidence: 75%
“…There are reports suggesting that proinflammatory cytokines – interleukin (IL) 6, IL-1βi, IL-8, vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF) – play an important role in ascites, hydrothorax or pleurocardia [ 13 ]. Numerous Meigs’ syndrome cases were described as related to increased levels of CA-125 [ 14 , 15 ]. CA-125 is a glycoprotein, in humans encoded by the MUC16 gene on chromosome 19 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%